In memoriam of Yurii Rogozhin - The staff of the Vladimir Andrunachievici Institute of Mathematics and Computer Science (Computer Science Journal of Moldova, 2019)
November 13, 2019 would be the 70th birthday of Prof. Yurii Rogozhin.